The role of local history in strengthening national identity in the era of society 5.0 - Danugroho, Agus (AGASTYA: JURNAL SEJARAH DAN PEMBELAJARANNYA, 2024)
National identity is a crucial element in building unity within a country, and history plays a central role in shaping that identity. However, sometimes the focus on national history can overlook local cultural roots and heritage that are integral to the larger national identity. An Merdeka curriculum that incorporates local history is an important instrument in linking national history with local cultural roots. Although the challenges of integrating local history are many, the resulting benefits, including an appreciation of cultural diversity, local pride, and a deeper understanding of national identity, provide a strong basis for continuing this endeavor. The type of research used is qualitative. The results of this study show the importance of local history in reinforcing national identity. The integration of local history in the curriculum not only deepens students' knowledge, but also provides a stronger foundation for shaping a national identity that is inclusive, values diversity, and strengthens the bond between local and national identity.